Evolution of the System of the Demonstrative Pronouns between Attic and Modern Greek. Refl ections in the Light of a Quantitative Analysis - Floristán, José Manuel (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2013)
Unlike ancient Greek, which had a system of demonstrative pronouns with three terms, Modern Greek basically has a two-terms system. This paper offers a diachronic analysis of the linguistic development between both stages by applying the dynamics-theory of H.-J. Seiler in the light of quantitative data from Greek authors of several periods between the 5th century BCE and the end of the Byzantine Period.
Keywords: System of the demonstrative pronouns; diachrony; restructuring dynamics; quantitative analysis.